Hubungan Intensitas Kebisingan Dengan Gangguan Pendengaran Pada Pengemudi Boat Pancung Di Pulau Belakang Padang Kota Batam Tahun 2017 - Ice Irawati (Stikes Syedza Saintika Padang, 2018)
Health is a basic human need and capital to live productively and efficiently. Health is not everything, but without health everything becomes meaningless. This is in accordance with Law no. 36 of 2009 on health, which clearly states that every person has the same rights in order to obtain the optimal health degree, for it held various health efforts by using health promotion / promotion (promotif), prevention of disease (preventive), Healing (curative) , And health care (rehabilitative).The purpose of this study to determine the Relation of Noise Intensity With Hearing Loss In Boat Pancung Driver In Island Belakang Padang Batam City Year 2017.This type of research is conducted by analytical method with cross sectional design. The sample number is 55 respondents with Simple Random Sampling method. The result of the research shows that there is relationship between noise intensity with hearing loss with P value = 0.000 then P <0,05.The conclusion that there is a significant relationship between noise with hearing loss. It is expected that managers provide education and training related to knowledge due to noise and prevention either through joint discussions or at meetings and evaluations conducted by managers, so drivers understand the dangers of noise and managers should always disseminate information about safety, personal protective equipment and other Other safety-related issues in preventing deafness.